Determining optimum harvest time under Mediterranean conditions: developing a new model for measuring L-malic acid concentration in red grapes - Olego, M. A.; Álvarez, J. C.; Tobes, A.; De-Paz, José M.; Coque, J. J. R.; Garzón-Gimeno, Enrique (Wiley Online Library, 2020)
Background and Aims: Malic acid concentration varies as berries develop, reaching its highest value just before veraison. Objective criteria for choosing the optimal harvest time require chemical or physicochemical measurements; the determination of malic acid concentration is one of these. The main aim of this work was to develop a predictive model to determine the malic acid concentration in grapes at harvest time as an alternative to commonly used methods, such as HPLC and enzymatic analysis. Methods and Results: The red grape cultivar Vitis vinifera L. Tempranillo was used in this study. Of the 11 predictive parameters measured, titratable acidity (TA) had the greatest relative importance as a predictor variable for estimation of the concentration of malic acid in must at harvest time. Conclusions: The daily average rainfall from harvest time to the next season sampling time, pH and TA and TA raised to the second power have been shown to be significant contributors in predicting malic acid concentration in grapes at harvest time. Significance of the Study: This work describes a multiple regression model that explains malic acid concentration in red grapes at harvest time.